Nanowire width dependence of data retention and endurance characteristics in nanowire SONOS flash memory. (September 2016) - Choi, Jin Hyung; Yu, Chong Gun; Park, Jong Tae
Abstract: The investigations on the nanowire width (W) dependence of memory performance including P/E (programming and erasing) speed, data retention time and endurance characteristics in nanowire SONOS flash memory have been performed through the measurement and the device simulation. From measured results, a narrow device has advantages in terms of a fast P/E speed and the endurance characteristics. However, a narrow device has disadvantage in terms of the decreased data retention time. Another disadvantage of a narrow device is expected to the large power consumption due to large GIDL (Gate Induced Drain Leakage) current. The device simulation was performed to explore the causes for a fast P/E speed, an enhanced endurance characteristics and the reduced data retention time in narrow devices. Highlights: Investigation on the nanowire width (W) dependence of memory performance in nanowire SONOS flash memory Narrow device has advantages in terms of a fast P/E speed and the endurance characteristics. Narrow device has disadvantage in terms of the decreased data retention time and power consumption.